Correction: Genome-Wide Association Study Reveals Multiple Loci Associated with Primary Tooth Development during Infancy ... : تصحيح: تكشف دراسة الجمعية على مستوى الجينوم عن مواضع متعددة مرتبطة بتطور الأسنان الأولية أثناء الطفولة ... - Demetris Pillas; Clive Hoggart; David M. Evans; Paul O'Reilly; Kirsi Sipilä; Raija Lähdesmäki; Iona Y. Millwood; Marika Kaakinen; Gopalakrishnan Netuveli; David Blane; Pimphen Charoen; Ulla Sovio; et al. (OpenAlex, 2010)
Tooth development is a highly heritable process which relates to other growth and developmental processes, and which interacts with the development of the entire craniofacial complex.Abnormalities of tooth development are common, with tooth agenesis being the most common developmental anomaly in humans.We performed a genome-wide association study of time to first tooth eruption and number of teeth at one year in 4,564 individuals from the 1966 Northern Finland Birth Cohort (NFBC1966) and 1,518 individuals from the Avon Longitudinal Study of Parents and Children (ALSPAC).We identified 5 loci at P,5610 28 , and 5 with suggestive association (P,5610 26 ).The loci included several genes with links to tooth and other organ development (KCNJ2, EDA, HOXB2, RAD51L1, IGF2BP1, HMGA2, MSRB3).Genes at four of the identified loci are implicated in the development of cancer.A variant within the HOXB gene cluster associated with occlusion defects requiring orthodontic treatment by age 31 years. ... : تطور الأسنان هو عملية وراثية للغاية تتعلق بعمليات النمو والتطور الأخرى، والتي تتفاعل مع تطور المركب القحفي الوجهي بأكمله. إن حالات عدم تطابق نمو الأسنان شائعة، مع كون تولد الأسنان هو الشذوذ التنموي الأكثر شيوعًا لدى البشر. أجرينا دراسة ارتباط على مستوى الجينوم للوقت الذي يحدث فيه أول ظهور للأسنان وعدد الأسنان في عام واحد في 4564 فردًا من مجموعة الولادة في شمال فنلندا لعام 1966 (NFBC1966) و 1518 فردًا من دراسة أفون الطولية للوالدين والأطفال (ALSPAC). حددنا 5 مواقع في P، 5610 28 ، و 5 مع ارتباط إيحائي (P، 5610 26 ). تضمنت المواقع العديد من الجينات مع روابط للأسنان وتطور الأعضاء الأخرى (KCNJ2، EDA، HOXB2، RAD51L1، IGF2BP1، HMGA2، MSRB3). الجينات في أربعة من المواقع المحددة متورطة في تطور السرطان. متغير HXO داخل مجموعة جين المرتبطة بالعيبات أو تتطلب العلاج حسب العمر 31 عامًا. ...